2013
DOI: 10.1007/s10911-013-9308-2
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Leptin Network: The Molecular Connection Between Obesity and Breast Cancer

Abstract: High plasma levels of leptin, a major adipocytokine produced by adipocytes, are correlated with increased fat mass in obese state. Leptin is emerging as a key candidate molecule linking obesity with breast cancer. Acting via endocrine, paracrine, and autocrine manner, leptin impacts various stages of breast tumorigenesis from initiation and primary tumor growth to metastatic progression. Leptin also modulates the tumor microenvironment mainly through supporting migration of endothelial cells, neo-angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 121 publications
1
48
0
2
Order By: Relevance
“…In obese subjects, increasing levels of circulating VEGF accompanied tumoral expression, which was linked to cancer patients with a poor prognosis [12,27]. This increase of VEGF was also shown in the tumors of obese mice [20]; several inflammatory adipokines, which were increased with obesity, contributed to breast carcinogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In obese subjects, increasing levels of circulating VEGF accompanied tumoral expression, which was linked to cancer patients with a poor prognosis [12,27]. This increase of VEGF was also shown in the tumors of obese mice [20]; several inflammatory adipokines, which were increased with obesity, contributed to breast carcinogenesis [21].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, obesity-associated metabolic syndrome and elevated insulin levels are tightly linked with inflammation [25]. Leptin is also known to induce the expression of pro-inflammatory, pro-tumorigenic cytokines in macrophages, including IL-1, IL-6 and TNF-α [59]. Other studies have shown the concomitant elevation of IL-1β and leptin with increased body mass in rats that drives the growth of mammary epithelium [60] and that leptin expression in pre-adipocytes can be induced by IL-1 and TNF-α secreted from ATM [61].…”
Section: Obesity and Cancermentioning
confidence: 99%
“…Leptin is the most important weight controlling adipokine in white fat tissue and thus has a key role in the relationship between obesity and cancer. It is reported to affect survival, migration, and growth of cancer cells by increasing the expression of antiapoptotic proteins; estrogen; pro-inflammatory cytokines, such as TNF-α and IL-6; and angiogenic factors, such as VEGF and hypoxia-induced factors (HIF-1α) (18,19,(71)(72)(73)(74). In a cell culture study that investigated the effect of leptin on breast cancer, leptin (obASC) from obese patients led to increased proliferation of ER-positive breast cancer cells, whereas no such effect was observed in case of leptin (InASC) from patients with BMI less than 25 kg/m 2 .…”
Section: Can Weight Loss Reduce the Incidence Of Breast Cancer?mentioning
confidence: 99%
“…The ranking for all groups was as follows: healthy control, control with light breast disease, patients with breast cancer, and patients with lymph node metastasis. Serum leptin levels in postmenopausal ER-positive breast cancer patients were found to be the lowest in clinical and pathologic classifications (72,73,76). Increased ectopic lipoaccumulation in obesity leads to tissue hypoxia, inflammation, and reactive angiogenesis, leading to changes in tumorigenesis and tumor characteristics (metastasis, invasion) (77).…”
Section: Can Weight Loss Reduce the Incidence Of Breast Cancer?mentioning
confidence: 99%